PENGEMBANGAN PENDIDIKAN ISLAM BERBASIS PLURALISME DALAM MENEKAN ANGKA RADIKALISME ATAS NAMA AGAMA DI INDONESIA - Nuhrodin Nuhrodin (KarismaPro, 2021)
faith, which first should not be more dominant with the exclusion of the second factor is faith as the substance. And faith is essential is faith that opens in the middle of the plurality of beliefs that exist. Or in another sense belief that being able to accept the existence of faith other than the faith itself.Islam as a religion kafah should have implied the deepest values about the importance of understanding the basics of pluralism which leads Muslims to interact amid the plurality of beliefs existing community. Live then how education is able to transfer value (values) are appropriately pluralism in the conception and practice so as to color the life of society with the understanding of religious pluralism and avoid thinking and radical movements